O TRABALHO E OS SEUS SENTIDOS: um estudo com profissionais atuantes na área de Psicologia Organizacional e do Trabalho em São Luís - MA - SILVA, Juliana Lima (2021)
It is known that the world of work has undergone constant transformations, observed since the first relationships established by man in society, such as the search for means to satisfy his needs, whether physical, psychological or material. Thus, since the first human associations, in prehistory or in tribal communities, man is organized for work within a social context that limits and hierarchizes him,and he still manages to develop. Nowadays, with the sale of the labor force, through the processes of added value of the capitalist organization, labor and the inherent subjective relationships are in constant evidence, due to the repercussions of this new work organization. In this context, serious damage to workers' physical and mental health is evidenced, through long working hours and the fast pace of production. It is, therefore, considering this reality, that the main objective was to understand the meanings that the psychologist attributes to his work, and how he mobilizes subjectively, thinking of him beyond his interventionist exercise. Thus, an empirical research of a qualitative and quantitative character was developed, with a review of the literature findings being initially made to deepen the topic addressed. Theoretically it was based on the Psychodynamics of Work, from the study of the categories: pleasure-suffering, mediation strategies and meaning of work, articulating with Dialectical Historical Materialism. For data collection, the study was divided into two moments: the first, with the application of a questionnaire with closed questions, developed on the Google Forms platform, the questionnaire allowed access to a number of twenty-seven professionals working in the area of POT in São Luís - MA, of which five participated in the second moment of data collection, the semi-structured interview. The analysis of qualitative data was performed based on Critical Discourse Analysis (ACD), by Fairclough. In conclusion, it was possible to observe the know-how and routines of these professionals, understanding the conflicts and challenges that appear in the real work of these subjects, understanding that the meaning at work does not come from a single aspect, but appears as a product of a series of experiences of the subject and their relationship with the countless facets of the working world. Thus, it was possible to observe the spaces of struggle in the professionals' work routine, showing the constant pressures that are experienced, as well as the work overload that directly affects the work prescribed by the organization. Another point found was the ethical dilemma that these subjects face when they need to act in ways that meet their moral principles and what resources and mobilizations they use in these situations. Pleasure also appears from the subject's own conceptions of work, in view of the understanding of its usefulness and the recognition processes of this work, by their peers and superiors.